Accurate sampling of undisturbed top sediment from grab sampler collected using aluminum tube and stainless-steel containers for shallow and deep-sea applications - Mutsumi Iizuka; Atsuko Amano; Takuya Itaki (MethodsX)
This study describes a sediment sampling protocol using a Kinoshita-type grab (K-grab) sediment sampler to collect and analyze microplastics (<5 mm) and macroplastics (>5 mm) in marine sediments. During the GB24 geological survey cruise aboard the Bosei-maru, 133 surface sediment samples were collected from depths of 20–800 m. The K-grab, equipped with a head-slide weight mechanism, enhanced sampling efficiency across various sediment types. For microplastics, stainless steel containers and J-shaped aluminum tubes minimized contamination while maintaining sample integrity. Macroplastics were separated using a 5 mm mesh and analyzed on board. Method verification confirmed high-spatial-resolution sampling with minimal contamination. These results demonstrate that the K-grab is a reliable tool for microplastic and macroplastic analysis, providing valuable data on plastic pollution in marine sediments. • This study describes a sediment sampling protocol using a grab sampler to collect and analyze microplastics (<5 mm) and macroplastics (>5 mm) in marine sediments. • During the survey, 133 surface sediment samples were collected from depths of 20–800 m, with microplastics handled using J-shaped aluminum tubes and stainless steel containers to minimize contamination while maintaining sample integrity. • Macroplastics were separated using a 5 mm mesh and analyzed on board. Method verification confirmed high-spatial-resolution sampling with minimal contamination.